Imbalance in the Demand and Supply of Library Science Professionals in Madhya Pradesh [Central India] - Chopra, Y. L. (Journal of Information and Knowledge, 2000)
The paper highlights the significance of academic and other libraries for provision of effective library services. Therefore, for optimum managerial accomplishment of libraries in general and academic libraries in particular proper professional manpower training in librarianship in India is very essential. Keeping this in view the article touches in brief, history of library science education in India with special reference to Madhya Pradesh. The stress is on the present scenario in library science education in the State. The contents of the paper projects how the library science education has been commercialized in the state by setting aside all norms of imparting professional education. The focus is on mushroom growth of Library Science Departments at college level. It openly discusses what, why and how of this trend of teaching library science at state level and its indifferent impact on future professional manpower generation in library science if the same trend continues. The paper concludes with concrete suggestions to check privatization and the falling standards of library science education in Madhya Pradesh by intervention at the level of Department of Higher Education, M.P. at one hand and its Universities on the other.